ESTIMATION DES BESOINS EN EAU DE LA CULTURE DE L’AIL PAR DIFFERENTES FORMULES - Kadi Kenza; Chergui Manel; Malkia Nabila; Hamli Sofia; Boukeria Sabah; Yahia Abdelouahab (European Scientific Journal, ESJ, 2014)
This research focuses on the estimated water requirements of growing garlic (Allium sativum L.) variety Messidrôme and determining its impact on the behavior of plants. We chose 04 methods to estimate the need for determining PET namely; PET wilaya Oum El Bouaghi (T1), evaporation of Piche (EVP, T2), the formula Blanney Criddle (T3), and the formula for Bouchet (T4) compared with non-irrigated control. To get a good garlic production with an optimum size of bulbs based on estimate irrigation through Blanney Criddle formula takes consideration of lighting and average temperature